2019
DOI: 10.1520/acem20190035
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Seismic Performance Levels of Corroded Reinforced Concrete Columns as a Function of Crack Width

Abstract: An experimental study was conducted for the prediction of the seismic performance levels of corroded reinforced concrete (RC) columns as a function of the initial corrosion crack widths. A full-scale accelerated-corrosion pool was used to corrode 25 full-scale RC columns. The initial crack widths at different levels of corrosion were measured for three different concrete strength levels: 9, 27, and 37 MPa. The seismic performance levels of corroded RC columns under combined cyclic lateral-displacement excursio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 17 publications
3
21
1
Order By: Relevance
“…As shown in Figure 13, although the compressive strength of the current study was within the limits of the model proposed by Yalciner et al, 28 the developed model underestimated the current experimentally measured reduction in the cross‐sectional area. This was because of the limited crack widths of the concrete after the corrosion propagation process.…”
Section: Resultscontrasting
confidence: 46%
See 4 more Smart Citations
“…As shown in Figure 13, although the compressive strength of the current study was within the limits of the model proposed by Yalciner et al, 28 the developed model underestimated the current experimentally measured reduction in the cross‐sectional area. This was because of the limited crack widths of the concrete after the corrosion propagation process.…”
Section: Resultscontrasting
confidence: 46%
“…Figure 19 shows the percentage of remaining energy capacity of the corroded RC columns in the present study and experimental data obtained from the study by Yalciner et al 28 The corrosion levels obtained from the study by Yalciner et al 28 are also shown in Figure 18 for comparison.…”
Section: Resultsmentioning
confidence: 69%
See 3 more Smart Citations